2021
DOI: 10.5713/ab.20.0791
|View full text |Cite
|
Sign up to set email alerts
|

The effect of light on follicular development in laying hens

Abstract: Objective: The oxidative stress status and changes of chicken ovary tissue after shading were studied, which is to determine the mechanism of the effect of shading on follicular development.Methods: Twenty healthy laying hens (40 weeks old) with uniform body weight and the same laying rate were randomly divided into two groups (the shading group and normal light group).In the shading group, the cage was covered to reduce the light intensity inside the cage to 0 without affecting ventilation or food intake. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…When we observed the ultrastructure of the ovaries, we found that a large number of granulosa cells were apoptotic during the brooding period [24], and the nuclei showed wrinkling and deformation, but the cell membranes were intact, and some of them showed foaming or apoptotic vesicles [25], while the apoptotic cells in the ovaries during the laying period were significantly fewer than those in the brooding period, and the antioxidant enzyme activities (SOD, CAT, GSH-PX) and oxidized free radicals (MDA, GSH, H 2 O 2 ) in the ovaries of geese during the brooding period were detected to be significantly higher. ROS can cause oxidative damage to cells, including the induction of apoptosis [26,27]. Therefore, we suggest that follicular atresia and apoptosis are closely related to oxidative stress in goose broods.…”
Section: Discussionmentioning
confidence: 86%
“…When we observed the ultrastructure of the ovaries, we found that a large number of granulosa cells were apoptotic during the brooding period [24], and the nuclei showed wrinkling and deformation, but the cell membranes were intact, and some of them showed foaming or apoptotic vesicles [25], while the apoptotic cells in the ovaries during the laying period were significantly fewer than those in the brooding period, and the antioxidant enzyme activities (SOD, CAT, GSH-PX) and oxidized free radicals (MDA, GSH, H 2 O 2 ) in the ovaries of geese during the brooding period were detected to be significantly higher. ROS can cause oxidative damage to cells, including the induction of apoptosis [26,27]. Therefore, we suggest that follicular atresia and apoptosis are closely related to oxidative stress in goose broods.…”
Section: Discussionmentioning
confidence: 86%
“…The separated plasma was stored at −20°C for subsequent studies. Levels of 8-OHdG, SOD, MDA, GSH-Px, CAT, MT as well as ROS were evaluated by ELISA with the help of a commercial kit (Shanghai Jianglai Biotechnology Co., Ltd., Shanghai, China), by following the protocol provided by the manufacturer ( Sihong et al, 2019 ; Hao et al, 2020b ; Cheng et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon in older chickens is connected with a reduced rate of follicle recruitment for rapid growth and a lengthy period of follicular growth and development [ 49 ]. Several factors, including the environmental conditions and nutrition supply, influence the decrease in egg production in laying chickens [ 50 ]. However, oocyte apoptosis, a failure to maintain the ovarian reserve due to the excessive activation of primordial follicles for rapid growth, elevated levels of reactive oxygen species (an oxidative stress condition), the formation of a high number of atretic follicles, and a decline in liver function are factors primarily associated with the gradual decrease in, and even cessation of, egg production in older chickens [ 51 , 52 , 53 ].…”
Section: Ovarian Follicles At Young and Old Agesmentioning
confidence: 99%